Digital Da’wah Beyond Social Media: Islamic Knowledge Circulation and Youth Engagement in Roblox and Discord Gaming Communities - Miftahul Jannah; Miftahur Rahmah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to analyze how Islamic knowledge circulates through immersive virtual spaces by examining da'wah practices in the Mario community that utilize the Roblox and Discord platforms. This research uses Arjun Appadurai's global cultural flow theory, specifically the concepts of technoscape and mediascape, to explain how digital technology infrastructure and media representation shape the circulation of Islamic knowledge in the digital religious space. The research uses a qualitative approach with digital ethnography methods through participatory observation over four months. Data were obtained through digital field observation, documentation, and interaction within the community, and then analyzed interpretatively based on ethnographic findings. This research argues that Roblox and Discord no longer merely function as media for da’wah communication, but have instead formed new religious social spaces that allow Islamic knowledge to be produced, circulated, and collectively experienced by their members. The research results show that the mediascape is represented through the formation of symbols, narratives, and virtual religious spaces that reconstruct religious practices in a digital environment, while the technoscape is reflected in the integration of various digital platforms that support the conduct of da’wah across space and time. Although it opens new opportunities for the expansion of digital da’wah, the virtual space also presents challenges such as issues of the legitimacy of religious authority, the authenticity of religious learning, and the potential for distraction due to the entertainment-oriented characteristics of the platform. This research expands the application of Appadurai's theory by demonstrating that online gaming platforms can serve as arenas for the circulation of Islamic knowledge within the global digital ecosystem.